2019
DOI: 10.1007/s00432-019-02864-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the EAU guidelines on Penile Cancer Treatment: European, multicentre, retrospective study

Abstract: Purpose The European Association of Urology (EAU) guidelines for penile cancer (PC) are exclusively based on retrospective studies and have low grades of recommendation. The aim of this study was to assess the adherence to guidelines by investigating the management strategies for primary tumours and inguinal lymph nodes. Methods We retrospectively reviewed the clinical charts of 176 PC patients who underwent surgery in eight European centres from 2010 to 2016. The stage and grade were assessed according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…In contrast, only 1.9% chose a too superficial procedure, laser therapy (0.6%) or resurfacing of the glans 1.3%. This is in line with the findings of Bada et al and Cindolo et al who also showed that physicians are more likely to choose a too radical rather than a too superficial surgical approach, a problem that is aggravated in less experienced centers [11,15]. On a positive note, [90% of the physicians that participated in our survey stated that penile-sparing surgery is common practice in their department.…”
Section: Availability Of Penile-sparing Surgery Predicts Great Guidelsupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast, only 1.9% chose a too superficial procedure, laser therapy (0.6%) or resurfacing of the glans 1.3%. This is in line with the findings of Bada et al and Cindolo et al who also showed that physicians are more likely to choose a too radical rather than a too superficial surgical approach, a problem that is aggravated in less experienced centers [11,15]. On a positive note, [90% of the physicians that participated in our survey stated that penile-sparing surgery is common practice in their department.…”
Section: Availability Of Penile-sparing Surgery Predicts Great Guidelsupporting
confidence: 90%
“…In one-third of the patients who did not receive correct local tumor therapy, this was due to surgeons' preference. In the majority of cases, this led to a more aggressive therapeutic approach [8]. This observation coincides with data of the Swedish national PeCa register.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Für die urologischen Erkrankungsbilder gibt es mittlerweile eine umfangreiche Sammlung solcher Leitlinien und v. a. in der Uroonkologie bereits einen großen Erfahrungsschatz mit einer entsprechenden Historie zum Umgang mit Leitlinien -sowohl bei der Erstellung als auch bei deren Nutzung und Verbreitung. Auch liefert die steigende Zahl an Untersuchungen zur Adhärenz der Leitlinien unbestritten Hinweise zu deren Nutzen [1][2][3] Hier steht eine Anzeige.…”
Section: Leitlinienadhärenzunclassified